DEVELOPING RIVER WATERSHEDS INTO TOURISM DESTINATIONS WITH AN ENVIRONTMENT BASED TOURISM (ECOPTOURISM) APPROACH: A CASE STUDY FROM SUNTENJAYA TOURISM VILLAGE, INDONESIA - Rachmat Syam (International Journal of Sustainable Competitiveness on Tourism, 2024)
Rural areas, especially those that are river basins, are very vulnerable to destructive changes from various activities, including tourism. This is also indicated as happening in the Suntenjaya Tourism Village, Indonesia. Therefore, it is necessary to study the application of ecotourism to mitigate the negative impacts of tourism on Cikapundung watershed conservation. The application of ecotourism to nature tourism activities in Suntenjaya Village was studied through descriptive research with a qualitative approach. Through observation, interviews, and secondary data collection, it was found that ecotourism has only been partially applied to nature tourism activities in Suntenjaya Tourism Village. The application of ecotourism can be promoted through the sustainable development orientation of Pokdarwis, but it is hindered by social conflicts and organizational duality in Suntenjaya Tourism Village